2000
DOI: 10.1016/s0378-1097(00)00170-1
|View full text |Cite
|
Sign up to set email alerts
|

Multicopy suppression of a gacA mutation by the infC operon in Pseudomonas fluorescens CHA0: competition with the global translational regulator RsmA

Abstract: The gacA gene of the biocontrol strain Pseudomonas fluorescens CHA0 codes for a response regulator which, together with the sensor kinase GacS ( = LemA), is required for the production of exoenzymes and secondary metabolites involved in biocontrol, including hydrogen cyanide (HCN). A gacA multicopy suppressor was isolated from a cosmid library of strain CHA0 and identified as the infC-rpmI-rplT operon, which encodes the translation initiation factor IF3 and the ribosomal proteins L35 and L20. The efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We have previously obtained genetic evidence that GacA indirectly regulates the expression of these structural genes at a posttranscriptional level, involving the RNA-binding protein RsmA as a downstream regulatory element (5)(6)(7)(8). In the present study, we have characterized a regulatory RNA termed RsmZ, which was found to bind to RsmA and, when overproduced, caused strong derepression of aprA and hcnA expression.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We have previously obtained genetic evidence that GacA indirectly regulates the expression of these structural genes at a posttranscriptional level, involving the RNA-binding protein RsmA as a downstream regulatory element (5)(6)(7)(8). In the present study, we have characterized a regulatory RNA termed RsmZ, which was found to bind to RsmA and, when overproduced, caused strong derepression of aprA and hcnA expression.…”
Section: Discussionmentioning
confidence: 69%
“…In P. fluorescens CHA0, RsmA is an important negative control element involved in the posttranscriptional control of secondary metabolism regulated by the GacS/GacA system (7,8). Therefore, it could be postulated that an RNA analogous to RsmB/CsrB would be required to counteract the repressing effects of RsmA on target genes and that the expression of this regulatory RNA would be directly or indirectly controlled by GacA.…”
mentioning
confidence: 99%
“…The lag between induction of gene expression and accumulation of detectable levels of pyoluteorin might be explained by slow rates of pyoluteorin biosynthesis or by posttranscriptional control mechanisms, like those affecting the antibiotics 2,4-diacetylphloroglucinol and hydrogen cyanide in the related P. fluorescens strains CHA0 and F113 (1,5,6,20). Transcripts of genes for biosynthesis of hydrogen cyanide and 2,4-diacetylphloroglucinol are sequestered by a small RNAbinding protein (RsmA), but a noncoding RNA, PrrB (RsmZ), whose expression is regulated by GacA/GacS, can in turn bind RsmA, and thus relieve RsmA suppression in these strains.…”
Section: Discussionmentioning
confidence: 99%
“…The sensor kinase homologue of the two-component transduction system LetA/LetS was shown to be required for the transcription of rpoS in E. coli and P. fluorescens (Mukhopadhyay et al, 2000;Whistler et al, 1998). Recently, several studies have provided evidence that the control of gene expression by the two-component system homologues of LetA/LetS in other Gram-negative bacteria, such as E. coli, Erwinia and Pseudomonas, is mediated in part by a CsrA/CsrBlike system (Blumer and Haas, 2000;Cui et al, 1995;Hyytiainen et al, 2001;Suzuki et al, 2002). CsrB, an untranslated RNA molecule, neutralises CsrA function by sequestering this regulatory protein and has been demonstrated to be under the control of the twocomponent system.…”
Section: Discussionmentioning
confidence: 99%